2007
DOI: 10.1002/anie.200605166
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Supramolecular Bidentate Ligands for Aqueous Organometallic Catalysis

Abstract: Supramolecular chemistry is one of the fastest growing areas of chemistry and greatly contributes to the development of numerous new innovative concepts. This is especially true in the field of organometallic catalysis where host-guest interactions have proved to be a powerful tool to elaborate new strategies aimed at improving the performances of catalytic entities.[1] Among them, the design of supramolecular bidentate ligands appeared as an elegant approach to stabilize organometallic complexes under catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Machut et al demonstrated that hydrophobic interactions between b-cyclodextrin derivatives and water-soluble phosphines enable the construction of self-assembled ligands in water. 198 A b-cyclodextrin in which one of the primary hydroxyl groups has been replaced by an amino substituent was used as the host (61, Fig. 17a).…”
Section: Formation Of Bidentate Ligandsmentioning
confidence: 99%
“…Machut et al demonstrated that hydrophobic interactions between b-cyclodextrin derivatives and water-soluble phosphines enable the construction of self-assembled ligands in water. 198 A b-cyclodextrin in which one of the primary hydroxyl groups has been replaced by an amino substituent was used as the host (61, Fig. 17a).…”
Section: Formation Of Bidentate Ligandsmentioning
confidence: 99%
“…The art of synthesizing efficient molecular receptors and phosphines has been of tremendous help in the understanding of the catalytic process and now opens fascinating opportunities in the area of biphasic aqueous catalysis. For example, the formation of inclusion complexes between modified CDs and appropriate water soluble phosphines can be advantageously used to design new water soluble self-assembled supramolecular bidentates ligands for aqueous organometallic catalysis [95,96]. …”
Section: Discussionmentioning
confidence: 99%
“…In this last case, the local bulkiness around the metallic centre of the obtained supramolecular adducts become too high and a steric decongestion by dissociation of the RAME--CD/phosphine inclusion complex from the metal occurs, leading to phosphine lowcoordinated complexes as schematically represented in Figure 8. The ability of phosphine 1 to form very stable inclusion complexes with chemically modified CDs has also been used to design water-soluble supramolecular bidentate ligand for aqueous organometallic catalysis [71]. Thus, the inclusion of phosphine 1 into the cavity of 6 I -amino-6 I -deoxycyclomaltoheptaose by the NH 2 -containing face resulted in the formation of a rigid chelating bidentate ligand, with the nitrogen and the phosphorus atoms on the same side of the supramolecular edifice.…”
Section: So 3 Namentioning
confidence: 99%